DETERMINING THE EFFECT OF PROBLEM-BASED LEARNING INSTRUCTIONAL STRATEGY ON NCE PRE-SERVICE TEACHERS’ ACHIEVEMENT IN PHYSICS AND ACQUISITION OF SCIENCE PROCESS SKILLS - Ukoh, Edidiong Enyeneokpon (European Scientific Journal, ESJ, 2012)
Physics is the foundation of science and technology. Students achievement in this subject at all levels of Education had been consistently poor. In an attempt to seek solution to this problem this study determined the effect of problem-based learning on NCE pre-service teachers’ achievement in physics and acquisition of science process skills. The study adopted a quasi experimental research design with 98 females and 94 males from six colleges of education in South Western Nigeria constituted the sample. A treatment group was exposed to the problem-based learning instructional strategy and a control exposed to the conventional lecture method. The treatment was found to have significant effect on pre-service teachers’ achievement in physics F(2,185) = 43.441, p <.05 and science process skills F(2,175) = 183.803, P<.05. In achievement in physics students exposed to problem-based learning obtain higher post test score (=51.98) than those exposed to conventional lecture method (30.23). Also students exposed to problem-based learning strategy obtained higher science process skills score (=73.67) than those exposed to convention lecture method =26.73. It is concluded that problem-based learning strategy improves students’ achievement in physics and acquisition of science process skills and is therefore recommended for use by lecturers in colleges of education.